Physicochemical and Antioxidant Properties of Carapa procera Seed Oil from Korhogo, Côte d’Ivoire - Touré, Daouda; Koné, Monon; kambiré, Didjour Albert; Gbekley, Efui Holaly; Gouri, Gohi Rodrigue; Traoré, Lanciné; Kabran, Faustin Aka; Kabkan, Ahmont Claude Landry; Bedi, Gustave; Djaman, Allico Joseph (Diponegoro University, 2026)
Vegetable oils are gaining increasing interest due to their diverse applications in the food, pharmaceutical and cosmetics sectors. Carapa procera D.C (Meliaceae) is a tree found in the forests of tropical Africa. In Côte d'Ivoire, the seed oil from this plant is especially recommended for food and skin care. This study aimed to characterize the physicochemical properties, fatty acid and antioxidant activity of C. procera seed oil extracted by traditional methods , in order to assess its potential as alternative edible oil, with possible complementary applications in personal care products. The sample oil was supplied by a local producer from Korhogo. Analytical methods for oils were employed using pharmacopoeia assays, AOAC standard methods such as moisture content, acidity, peroxide value, saponification index, iodine value, impurity level and pH. Methyl esters were derived from the oily mixtures through an esterification process and were analyzed by GC/FID and GC/MS systems. The antioxidant activity was investigated using the DPPH radical scavenging method. C. procera oil is dominated by unsaturated fatty acids (59.2%, versus 38.7% saturated fatty acids). A total of fifteen free fatty acids were identified through their methyl esters. They represent 97.9% of the total chemical composition. The three main compounds are oleic acid (49.1 %), palmitic acid (28.5%) and stearic acid (8.3%). C. procera oil showed low antioxidant activity (IC50 > 400 µg/mL) compared with vitamin C (IC50=7.99 µg/mL). Further studies will investigate the antibacterial and anti-inflammatory properties of C. procera oil to better understand its potential as a functional ingredient in food system, with additional possibilities for non-food uses.